Study about Model Independent Genetic Mutations through Trends in Increase in Entropy - Sharma, Preet (New Frontiers in Physical Science Research Vol. 8, 2023)
The present study will discuss the statistical physics of model independent mutations. We will show that the entropy of a successful mutation and a failed mutation is different from the entropic aspects and the range in which the entropy of both types of mutations lie. A mutation is characterised by a change in the genetic sequence. A single nucleotide base, which serves as the building block of DNA, can be changed by a mutation to another nucleotide base. Larger mutations that affect numerous genes on a chromosome are possible. We have used statistical physics to define the partition function of an ensemble. Based on the partition function we have expressed how to calculate physical quantities such as average energy and entropy. The entropy of all processes increases. This is true even for biological systems. We have shown the difference between the entropy of a successful mutation and a failed mutation. We have shown how the entropy of a successful mutation differs from that of a failed mutation. This opens up future research opportunities where we can apply this to specific biological systems. Our future work is to study a specific type of mutation and see how the basics of statistical and thermodynamical physics explain the mutations from an entropy understanding.